LEO Satellite Internet of Things Access Technology Based on Beamforming - Xuxu XIE; Xiaojin DING; Tao HONG; Gengxin ZHANG (天地一体化信息网络)
The integration of terrestrial communication and satellite communication for internet of things (IoT) is the inevitable trend of the development of wireless communication network, to achieve the vision of the connection of everything.As a supplement to terrestrial IoT, satellite IoT can make up the fl aws of terrestrial IoT.However, with the expansion of IoT scale, it will be diffi cult for satellites to meet the communication needs of increasing number of IoT terminals, because the problem of limited satellite load will become increasingly prominent.Multiple-input multiple-output (MIMO) technology is the key technology of terrestrial 5G, and also an important research direction of satellite communication in the future 6G.The beamforming(BF) technology was introduced in MIMO into the low earth orbit (LEO) satellite based IoT, to made full use of spatial resources and signifi cantly improved system capacity.In view of the implementation conditions of BF technology and the characteristics of satellite IoT, several related issues were discussed, included channel model, BF criterions, load balancing access technology of one satellite and cooperative BF access technology of several satellites.